A fundamental investigation into aspects of the physiology and biochemistry of the stratum corneum in subjects with sensitive skin. (25th May 2016) - Raj, N.; Voegeli, R.; Rawlings, A. V.; Doppler, S.; Imfeld, D.; Munday, M. R.; Lane, M. E.
Abstract: Background: Sensitive skin is a poorly understood skin condition. Defects in stratum corneum (SC) barrier function and/or extrasensory neuronal networks in the epidermis are believed to be involved in the problem. Objectives: This study aimed to unravel the relationships between bleomycin hydrolase (BH) and calpain‐1 (C‐1), pyrrolidone carboxylic acid (PCA) levels, corneocyte maturation, transglutaminase (TG) and plasmin activities on the cheeks of subjects with sensitive skin. Methods: Forty‐eight female Caucasian subjects, Fitzpatrick skin phototypes II–III, with self‐perceived sensitive facial skin, were assessed and underwent a capsaicin reactivity test. Expert grading of skin condition was conducted as well as the measurement of transepidermal water loss (TEWL), skin capacitance, SC cohesion and SC integrity. BH, C‐1 and plasmin activities were measured as well as PCA levels, plasmin and TG activity. Differential Nile red and involucrin immunostaining was performed to assess corneocyte maturation and size. Results: About 52% of the subjects reacted to capsaicin. There were no significant differences between the capsaicin‐sensitive and non‐capsaicin‐sensitive subjects with reference to skin grading, TEWL, skin capacitance and SC cohesion. PCA levels and BH activity were lowest in the capsaicin‐sensitive panel ( P < 0.05) and were correlated in non‐capsaicin‐sensitive subjects ( r = 0.72). The activity of TG was significantly lower (48%) in the capsaicin‐sensitive subjects ( P < 0.001) and their corneocytes were less mature and smaller ( P ≤ 0.05). SC was estimated to be thinner (6.87 ± 0.28 vs. 8.68 ± 0.26 μm; P = 0.001) in the capsaicin‐sensitive subjects with a corresponding shorter SC path length (83.2 ± 4.4 μm and 113.1 ± 4.5 μm; P = 0.001). Conclusions: Despite the physiological similarities between the two groups of sensitive skin subjects, differences in their biochemistry were clearly evident. Lower levels of PCA, BH and TG activities together with a greater number of smaller and immature corneocytes indicate inferior SC maturation in the capsaicin‐sensitive subjects. The reduced maturation of corneocytes and thinner SC likely contributes to a greater penetration of capsaicin and the associated increased skin sensitivity. Abstract : Sensitive skin is a poorly understood skin condition. This study aimed to unravel the relationships between bleomycin hydrolase (BH) and calpain‐1 (C‐1), pyrrolidone carboxylic acid (PCA) levels, corneocyte maturation, transglutaminase (TG) and plasmin activities on the cheeks of subjects with sensitive skin. Lower levels of PCA, BH and TG activities together with a greater number of smaller and immature corneocytes suggest there is inferior SC maturation in the capsaicin‐sensitive subjects. Résumé: Contexte: La peau sensible est une condition de la peau mal comprise. Des défauts dans la fonction de barrière de la couche cornée (SC) et / ou dans les réseaux neuronaux extrasensorielles dans l'épiderme sont soupçonnés d'être impliqués dans le problème. Objectifs: Cette étude visait à démêler les relations entre bléomycine hydrolase (BH) et calpaïne‐1 (C‐1), du taux d'acide carboxylique (PCA) pyrrolidone, de la maturation des cornéocytes, de transglutaminase (TG) et des activités de la plasmine sur les joues de sujets avec peaux sensibles. Methodes: Quarante‐huit sujets caucasiens féminins, avec une peau de phototype Fitzpatrick II‐III, avec autoperception d'une peau sensible au niveau du visage ont été évalués et ont subi un test de réactivité à la capsaïcine. Un classement Expert de l'état de la peau a été réalisé ainsi que la mesure de la perte d'eau transépidermique (TEWL/PIE), de la capacité de la peau, de la cohésion et de l'intégrité du SC. BH, C‐1 et les activités de plasmine ont été mesurées, ainsi que les taux de l'APC, de plasmine et de l'activité TG. La coloration différentielle au Nil rouge et bar immunocoloration de l'involucrine a été réalisée pour évaluer la maturation et la taille descornéocytes. Resultats: 52% des sujets ont réagi à la capsaïcine. Il n'y avait pas de différences significatives entre les sujets sensibles à la capsaïcine et non sensibles à la capsaïcine par rapport au classement de la peau, de la PIE, de la capacité de la peau et de la cohésion de SC. Les taux de l'APC et de l'activité BH étaient les plus bas dans le panel des personnes sensibles à la capsaïcine (p <0, 05) et ont été corrélés chez les sujets non‐sensibles à la capsaïcine (r = 0, 72). L'activité de TG était significativement plus faible (48%) chez les sujets sensibles à la capsaïcine (p <0, 001) et leurs cornéocytes étaient moins matures et plus petits (p ≤ 0, 03). Le SC a été à trouvé être plus mince (6, 87 ± 0, 28 vs 8, 68 ± 0, 26 μ m; p = 0, 001) chez les sujets sensibles à la capsaïcine avec une longueur de trajet de SC plus courte correspondant (83, 2 ± 4, 4 μ m et 113, 1 ± 4, 5 μ m; p = 0, 001) . Conclusion: Malgré les similitudes physiologiques entre les deux groupes de sujets à peaux sensibles, les différences dans leur biochimie étaient clairement évidentes. Les taux plus bas d'activités PCA, BH et TG ainsi qu'un plus grand nombre de cornéocytes petits et immatures indiquent une inférieure maturation du SC chez les sujets sensibles à la capsaïcine. La maturation réduite de cornéocytes et le SC plus mince contribuent probablement à une plus grande pénétration de la capsaïcine et à la sensibilité associée accrue de la peau.